Macroeconomic analysis and economic policy based on parametric control - Ashimov, Abdykappar A.; Sultanov, Bahyt T.; Adilov, Zheksenbek M.; Borovskiy, Yuriy V.; Novikov, Dmitriy A.; Nizhegorodtsev, Robert M.; Ashimov, Askar A. (Springer Science+Business Media, LLC, 2012)
After the transition to free economy, governments of the former Soviet republics realized that in spite of becoming a part of the shaky international economic order, their individual economic success can be assured by rational national economic policies that in addition to the fundamental law of supply and demand govern the economic mechanism sensitive to both external and internal phenomena. Originally published in Russian and now translated in English, this book by Dr. A. Ashimov and his colleagues offers a novel theory providing a numerically-justifiable approach to the solution of major economy control problems that are faced by virtually every government in the world. First, they developed and validated numerous mathematical models describing complex interactions between economic and social factors thus enabling the decision makers to foresee the outcomes of their decisions. Second, on the basis of these models the authors formulated the appropriate control problems that could be interpreted as achieving the transition to the desirable economic regimes and maintaining these regimes in spite of initial conditions and both external and internal perturbations.Macroeconomic Analysis and Economic Policy Based on Parametric Control offers a novel, highly mathematical approach to the solution of very realistic economy control problems. It presents a good example of the application of mathematical modeling, advanced control theory, and model-based decision making that could be adopted by researchers and graduate students specializing in economics, control, and relevant areas of research, addressing their own research problems.